Entheseal changes: the role of Portuguese research - Cardoso, Francisca Alves (2017)
In this paper, we present a review of research in Portugal on entheseal changes (EC), widely used to record activity-patterns. This is explored chronologically and thematically, from the beginning of the research on EC addressing the development of research methods tested through their use in identified collections, which sought to infer if the physical activity leads to EC, to a workshop in 2009, dedicated to EC, through to the recently published outputs of the working groups set up at that meeting. We will also discuss the role of individuals and the world class identified skeletal collections. Key trends include the systematic development of recording methods, their testing and the interrogation of the interplay of biology and society in occupation. The recent outputs of all the working groups will inform current and future research, meaning that the Portuguese role in the study of entheses will be long-lived and continue to be of international significance.